Literature Review History Social Science - Sriyatun (Pena Edukasia, 2024)
Social Sciences (Social Sciences) comes from United States educational literature. In English IPS is defined as "Social Studies." This term was first used as the name of an institution called the Committee of Social Studies. Social science was born in the 17th and 18th centuries by Habbes and Locke from 1920-1930. The history of social science focused on the impact of violations. From 1930 to 1940, various consequences of depression as a result of crime arose. The method used in the journal is a literature review taken from articles from 1998 to 2022. The definition of social studies according to Edgar Bruce Wesley in 1937 (Barr, Bart and Shermis, 1977:2), namely: The social studies are the social sciences simplified for pedagogical purposes” Social Sciences are simplified for educational purposes. Which includes aspects, such as science, history, economics, politics, sociology, anthropology, psychology, geography and philosophy, which are practically used in learning in schools and universities. The research used a literature review in four journals from 2018 to 2023. The connection between the history of social sciences and social science learning in schools needs to be understood that the bond between history and social sciences cannot be broken. Basically, history is a diachronic science. The meaning of this is that the knowledge is presented lengthwise over time and narrowly over space. On the other hand, social science is a synchronic science. The meaning of this is that knowledge is described as narrowing over time and expanding over space.